Spillovers in space and time: Where spatial econometrics and Global VAR models meet - Jean Paul Elhorst; Eugen Tereanu; Marco Gross (European Central Bank (ECB), 2018)
We bring together the spatial and global vector autoregressive (GVAR) classes of econometric models by providing a detailed methodological review of where they meet in terms of structure, interpretation, and estimation methods. We discuss the structure of cross-section connectivity (weight) matrices used by these models and its implications for estimation. Primarily motivated by the continuously expanding literature on spillovers, we define a broad and measurable concept of spillovers. We formalize it analytically through the indirect effects used in the spatial literature and impulse responses used in the GVAR literature. Finally, we propose a practical step-by-step approach for applied researchers who need to account for the existence and strength of cross-sectional dependence in the data. This approach aims to support the selection of the appropriate modeling and estimation method and of choices that represent empirical spillovers in a clear and interpretable form.
Keywords: C33; C38; C51; 330; Weak and strong cross-sectional dependence; spatial models; GVARs; spillovers